HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD GUGUS III KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Dwi Rahmatul Aini; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the low learning result of students' mathematics. Researchers suspect that one of the factors penyebanya is the lack of motivation of students to math lessons. The purpose of this study is to determine the significant relationship between learning motivation on the results of learning mathematics. This study is expected to provide benefits and images to determine the relationship between learning motivation with learning outcomes and how much influence between learning motivation and learning outcomes. This research was conducted in Class IV SD Cluster III of Rumbai Pesisir District. This research uses quantitative descriptive research that aims to find and describe the picture of the relationship between learning motivation and learning outcomes. The data obtained is quantitative data or numbers that can be viewed from the results of the analysis that is in the form of questionnaire data and learning result data. The population of the study amounted to 287 students, samples taken as many as 86 students. The results of this study there is a relationship between motivation with learning outcomes with correlation coefficient of 0.304. then Ha is accepted, meaning there is a significant relationship between the variable X (learning motivation) with variable Y (learning outcomes) with the level of relationship between low variables, significant relationships can be seen from titung of 2.920 and ttable of 1.989. If thitung ≥ ttabel, 2,920 ≥ 1,989 then Ho rejected which means there is a significant relationship between learning motivation with student learning outcomes. Motivation in learning gives a relationship of 9.2% and the rest of 90.8% influenced by other factors.. Keywords : Learning Motivation, Mathematics learning outcomes